Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s00221-017-5147-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mirror neuron system activation during action observation alone and action observation with motor imagery tasks

Abstract: This study aimed to explore the relationship between action observation (AO)-related corticomotor excitability changes and phases of observed action and to explore the effects of pure AO and concurrent AO and motor imagery (MI) state on corticomotor excitability using TMS. It was also investigated whether the mirror neuron system activity is muscle-specific. Fourteen healthy volunteers were enrolled in the study. EMG recordings were taken from the right first dorsal interosseous and the abductor digiti minimi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 46 publications
1
14
1
2
Order By: Relevance
“…According to similar studies [8,55,56], it could be used for post-stroke treatment, spinal cord injury (SCI) patients, trauma, etc. Moreover, as [57] have shown, by simultaneously combining motor imagery and action observation when compared to simply observing the action, we see an enhanced corticomotor excitability that might result from the activation of mirror neurons. This promising conclusion highlights that the results obtained in this study might be applied to the rehabilitation of medullary-injured patients.…”
Section: Discussionsupporting
confidence: 58%
“…According to similar studies [8,55,56], it could be used for post-stroke treatment, spinal cord injury (SCI) patients, trauma, etc. Moreover, as [57] have shown, by simultaneously combining motor imagery and action observation when compared to simply observing the action, we see an enhanced corticomotor excitability that might result from the activation of mirror neurons. This promising conclusion highlights that the results obtained in this study might be applied to the rehabilitation of medullary-injured patients.…”
Section: Discussionsupporting
confidence: 58%
“…Here as well, no superiority effect of AO+MI on muscle function was found when compared to the AO+Attention, while both AO+Attention and AO+MI outperformed the control condition in terms of total force. Simultaneous MI and AO were found to significantly enhance corticomotor excitability in comparison to pure AO (Wright et al, 2016;Cengiz et al, 2018). Being instructed to observe passively, or with the intent to imitate the observed movement, or while simultaneously and actively imagining self-performance of the movement during observation facilitated corticospinal excitability to a greater extent than observation of a static hand.…”
Section: Introductionmentioning
confidence: 87%
“…In these networks, the same neural areas are responsible for both an observed action performed by others and the actual execution of the action [5, 13–15]. Action observation is applied in stroke rehabilitation because it may prime the motor system for subsequent motor practice and enhance the patients' performance by activating these networks [5, 1618].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies involving humans have shown that an action observation-execution matching mechanism is present in specific regions of the frontal and parietal lobes [19, 20]. However, many imaging studies on action observation have been conducted on healthy controls [14, 16, 1921]. The experimental studies involving stroke patients have had considerable disparities among the stroke-onset phases (subacute or chronic stroke) of the recruited patients and the sizes (5 to 24) of the study samples.…”
Section: Introductionmentioning
confidence: 99%